Hubungan Pengetahuan, Sikap dan Peran Petugas Kesehatan Dengan Perilaku Keamanan Pangan Pada Ibu Yang Mempunyai Balita di Dusun Kepuh Wetan, Kabupaten Wonogiri. - Dyah Suryani; Mudrik Suzada (Universitas Muhammadiyah Semarang, 2023)
ABSTRACTMothers who have toddlers have become imperative to implement food safety behavior. Moreover, if there are vulnerable individuals in the family such as a toddler, the risk that often arises is the incidence of diarrhea in toddlers. This study aims to determine the relationship between knowledge, attitudes, and roles of health workers with food safety behavior in mothers who have toddlers in Kepuh Wetan Hamlet. The research used an analytic observational method with a cross-sectional research design. The number of samples was 51 respondents with proportional random sampling technique. Data analysis using the chi-square test with 95% CI (α = 0.05). The results showed that there was a relationship between attitudes (p-value = 0.001) and the role of health workers (p-value = 0.038) with food safety behavior in mothers with toddlers. While the knowledge variable (p-value = 0.406) did not show a significant relationship. Therefore, the mother's attitude and the role of health workers affect food safety behavior in mothers who have toddlers while knowledge does not. It is hoped that the local government will improve food safety training for every woman of childbearing age.